Energy and Protein Requirements for the Maintenance of Growing Male Sika Deer (Cervus nippon) - Bao, Kun; Wang, Xiaoxu; Wang, Kaiying; Li, Guangyu; Liu, Hanlu (Frontiers in Veterinary Science, 2021)
The objective of this study is to study the effects of dietary intake levels on energy metabolism, carbon (C), and nitrogen (N) balance and to determine the maintenance requirements of energy and protein for sika deer during their growing period. A total of 16 one-year-old male sika deer with similar body weight (BW) (63.25±2.42 kg) were selected, with four animals per feed intake level. The feed intake levels of the four groups for deer were 40%, 60%, 80%, and 100% of the recommended amount, respectively. The nutrient digestibility and methane production were measured through digestion trials and respiratory trials. A 4×4 Latin Square design was performed in a respirometry trial. The results show that the apparent digestibility of C and N gradually increased as the level of feed intake decreased. Furthermore, with a decrease in feed intake level, the metabolic energy intake (MEI), heat production (HP), and retained energy (RE) of sika deer significantly decreased (P<0.01). The requirements of metabolic energy for maintenance (MEm) and net energy for maintenance (NEm) of growing deer are 251.17 kJ kg-1BW0.75d-1 and 223.62 kJ kg-1BW0.75d-1, respectively, as estimated according to the logarithmic regression equations between HP and MEI. The net N requirement for maintenance (NNm) and net protein requirement for maintenance (NPm) of growing deer based on the linear relationship between retained nitrogen (RN) and daily nitrogen intake (NI) were 251.8 mg kg–1BW0.75d–1 and 1.57g kg–1BW0.75d–1, respectively. The NEm and NPm values obtained from this experiment fill the gap in net energy and protein requirements and serve as basic data for establishing the nutritional standards for sika deer breeding in China.